1981
DOI: 10.1172/jci110400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frequency, tidal volume, and lung volume on CO2 elimination in dogs by high frequency (2-30 Hz), low tidal volume ventilation.

Abstract: A B S T R A C T Recent studies have shown that effective pulmonary ventilation is possible with tidal volumes (VT) less than the anatomic dead-space if the oscillatory frequency (f) is sufficiently large. We systematically studied the effect on pulmonary CO2 elimination (VCO2) of varying f (2-30 Hz) and VT (1-7 ml/kg) as well as lung volume (VL) in 13 anesthetized, paralyzed dogs in order to examine the contribution of those variables that are thought to be important in determining gas exchange by high frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(34 citation statements)
references
References 14 publications
(34 reference statements)
1
33
0
Order By: Relevance
“…Perhaps it is not appropriate to think of an optimal frequency or an optimal V, in isolation. Slutsky et al (3,4 ) found C02 elimination to be dependent on V,,, as determined by the product of oscillatory frequency and V,. Slutsky concluded that although V,,, is an important factor in determining CO2 elimination, frequency and V, have independent effects with V, having a Veater effect on C 0 2 elimination than frequency at any given V,,,.…”
Section: Frequency (Hz)mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it is not appropriate to think of an optimal frequency or an optimal V, in isolation. Slutsky et al (3,4 ) found C02 elimination to be dependent on V,,, as determined by the product of oscillatory frequency and V,. Slutsky concluded that although V,,, is an important factor in determining CO2 elimination, frequency and V, have independent effects with V, having a Veater effect on C 0 2 elimination than frequency at any given V,,,.…”
Section: Frequency (Hz)mentioning
confidence: 99%
“…We observed that many combinations of frequency and V, produced equivalent blood gas tensions and that the composite variable f x V : was a good descriptor of our mean arterial blood gas tensions during HFOV in healthy rabbits. Others have found that different combinations of frequency, V, and Paw can produce equivalent blood gas tensions (3,4) but the resultant pressure swings in the trachea and alveolus may not be equivalent. Near the resonant frequency of the respiratory system, pressure swings in the alveolus may exceed those at the airway opening during HFOV (8,9).…”
mentioning
confidence: 99%
“…This characteristic is not confined to HFFI ventilation because VT larger than dead space have also been reported during jet ventilation (6,20,21). However, unlike other forms of HFV, in which VT decreases with increasing ventilation rate (9,22,23), the VT recorded HFFI were independent of ventilation rate (Fig. 3).…”
Section: Discussionmentioning
confidence: 70%
“…62 Oscillator settings include oscillatory power setting (magnitude of membrane displacement), frequency (f), in Hertz (Hz), inspiratory to expiratory ratio, position of the membrane, endotracheal tube (ETT) length and diameter, and the presence of ETT leakage. 20,66,67 The ETT constitutes the major work load to the oscillator and is an important determinant of V T . 68,69 V T is proportional to the ETT inner cross-sectional area, because the impedance of the ETT exceeds the impedance of the lung.…”
Section: Best Hfov Approach and Oscillator Settings For Ventilationmentioning
confidence: 99%